Strategies for Thrombus Management in STEMI Interventions - Vinall, Phil (MD Conference Express, 2011)
This article discusses a retrospective study that investigated the impact of thrombus burden on clinical outcomes in 812 consecutive patients who were treated with drug-eluting stents.